Purchase Intention and Satisfaction of Online Shop Users in Developing Countries during the COVID-19 Pandemic - García-Salirrosas, Elizabeth Emperatriz (2022)
The aim of the research is to gain an understanding of consumer behavior in developing countries in the electronic environment. For this purpose, the four constructs of the PREVEINCOSA scale were analyzed: purchase intention as the dependent variable and trust, perceived value, and satisfaction as the determining variables of the former. For this purpose, by means of convenience sampling, an online questionnaire was shared with citizens in Mexico, Peru, and Colombia. A total of 330 questionnaires were collected from people who knew or had bought clothes in an online shop of the small company. Structural equation modeling (SEM) was used to validate the model and test the hypotheses. The results indicate that trust and satisfaction directly and positively influence value perception and online purchase intention and that value perception directly and positively influences online purchase intention of the small business consumer in Mexico, Peru, and Colombia. These results may be useful for the small fashion business sector in developing countries since it is observed that the online sales channel is not yet developed, which makes it necessary to develop strategies to reach customers in a more effective way. On the other hand, given the importance of this sector for the economy of developing countries, this study can be useful to governments who can establish public policies to provide training and technical assistance to benefit the development and competitiveness of this sector.